AB1245 Aortitis: Diagnosis by positron emission tomography (PET). (23rd January 2014) - Bejerano, C.; Blanco, R.; Calvo, J.; Narváez, J.; Peirό, E.; Pérez-Martín, I.; Alonso, J.; Rueda-Gotor, J.; Corrales, A.; Peña, J.L.; Martínez, I.; Carril, J.M.; et al.
Abstract : Background: Non-infectious aortitis is often an underdiagnosed and potentially serious clinical entity. Although giant cell arteritis (GCA) is considered to be the most common cause of aortitis, it may also be idiopathic or associated with other conditions. Clinical manfiestations are frequently nonspecifc leading to inapropriate delay to the diagnosis. Methods: Multicenter study of three hospitals of patients diagnosed as having aortitis by F18-FDG PET. Results: Twelve patients (8 women/4 men) with a mean age of 68.4±12.7 years were diagnosed with aortitis by F18-FDG PET (TABLE ). The median [interquartile range] of delay to the diagnosis was 12 [2-20] months. Aortitis was idiopathic (5 cases), associated with biopsy-proven GCA (n=4), Sarcoidosis (n=1), Ulcerative Colitis (n=1), and Takayasu arteritis (n=1). The most frequent symptoms were: A) Polymyalgia rheumatica (PMR) in 8 cases (67%), that was atypical in 5 of them. B) Fever and/or general syndrome in 6 cases (50%). And C) Severe low back pain in 4 cases (33%). Laboratory data disclosed anemia in all cases and high ESR in most cases (78.1±38.3 mm/1st hour). PET showed involvement of A) the whole aorta, thoracic aorta and/or supra-aortic vessels in 91% and B) involvement of arteries of the lower extremities in 50%. Conclusions: F18 FDG-PET is a useful tool to confirm the diagnosis of aortitis. Atypical PMR, non-specific general syndrome, and/or unexplained severe low back pain along with anemia and elevated ESR may be red flags to suspect this condition. Disclosure of Interest: None Declared